CPE and CPAS. - Ho, Ming Wai. (2008)
This study seeks to determine the behavioral impact of Continuing Professional Education (CPE) on both the accounting and auditing profession in Singapore. Also, it seeks to examine the profession's members' attitudes with regards to the CPE programme.